Letter - Stolz, George
030-0084-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU St/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter F I de Sol No. 778 27th August 1938. Mr. H. V. Tewson, LONDON. Dear Comrade Tewson, We are indeed grateful for the cheque for five thousand pounds from the Mineworkers' Federation, which has been duly received here. This is a magnificent contribution, especially in view of the fact that it is donated in addition to the funds which will be applied for the children's homes, and it is especially appreciated at the present time of increasing need in Spain. Steps are at once being taken to use this money for the purchase and despatch of the most necessary articles. With many thanks , Yours sincerely, G. Stolz, Assistant Secretary: Enc : Formal receipt. 292/946/30/84